2014
DOI: 10.17221/7418-pse
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis sensitivity to NH<sub>4</sub><sup>+</sup>-N change with nitrogen fertilizer type

Abstract: N-fertilization type affected differently tomato growth. In the field experiment, hydroponic cultures were conducted using NO 3 -N (5 mmol); mixture of KNO 3 -N (3 mmol) and (NH 4 ) 2 SO 4 -N (2 mmol); NH 4 + -N (5 mmol) or urea (5 mmol) as nitrogen source. Compared to nitrate, ammonium and urea had negative effects on morphology and dry matter production. Effects of the different nitrogen forms were investigated by measuring several photosynthesis parameters and chl a fluorescence. Two different significant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In addition, NH4+ can be absorbed through aquaporins, non‐selective cation transporters and K transporters, increasing the risk of exposure to excess NH4+ concentrations (Bittsánszky et al., 2015). In this context, the toxicity of NH4+ results in a lower accumulation of cations such as K, Ca and Mg (Nasraoui‐Hajaji & Gouia, 2014), as observed in this study (Figure 1c–e). Since K + and NH4+ are very similar in terms of valence and ionic radius, they may not be distinguishable by the membrane‐bound carrier.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, NH4+ can be absorbed through aquaporins, non‐selective cation transporters and K transporters, increasing the risk of exposure to excess NH4+ concentrations (Bittsánszky et al., 2015). In this context, the toxicity of NH4+ results in a lower accumulation of cations such as K, Ca and Mg (Nasraoui‐Hajaji & Gouia, 2014), as observed in this study (Figure 1c–e). Since K + and NH4+ are very similar in terms of valence and ionic radius, they may not be distinguishable by the membrane‐bound carrier.…”
Section: Discussionsupporting
confidence: 77%
“…However, NH4+ has the disadvantage of being toxic depending on its concentration in the culture medium and the tolerance of the plant (Salsac et al., 1987). Among the consequences of NH4+ toxicity, the decrease in the accumulation of cations such as K, Ca and Mg is notable (Nasraoui‐Hajaji & Gouia, 2014; Schittenhelm & Menge‐Hartmann, 2006). The roots of cotton plants can experience.N - NH4+ For example, fertilization with 150 kg/ha of N resulted in 5.5 mmol/L of NH4+ in the soil solution (Foloni et al., 2006), but in cotton fields, higher doses of N are studied, such as 180 kg/ha (Raphael et al., 2019), which can lead to higher concentrations of NH4+ in the soil solution.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic levels of NH 4 + in vegetable tissues are produced when the conversion rate of NH 4 + into amino acids becomes less than the rate of absorption and cellular production for the catabolism of amino acids, nitrate reduction, and photorespiration (Hirel et al 2007). Another consequence of NH 4 + toxicity is that it reduces the accumulation of cations such as potassium, calcium, and magnesium, which are all essential nutrients for plants (Nasraoui-Hajaji and Gouia 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was thus concluded that tomato leaves treated with 25%AN:75%NN (T4) or NN: UN (T10–T12) can obtain more light energy and change the direction of light energy absorbed in PSII, which was consistent with the results of Osório et al [ 65 ]. Nasraoui-Hajaji et al [ 66 ] observed that tomato plants receiving ammonium nitrogen or amide nitrogen exhibited lower rates of CO 2 assimilation, stomatal conductance, and transpiration compared to those supplied with exclusively NO 3 − -N as the nitrogen source. Furthermore, the inclusion of nitrate in the nitrogen supply mitigated the reduction in these parameters.…”
Section: Discussionmentioning
confidence: 99%